0014 Social media for injury and violence prevention. learning how to use social and digital communications to effectively reach and engage with your audiences. (26th April 2015) - Mehta, Rupal
Abstract : Statement of purpose: In order to maximise injury and violence professionals' collaboration potential in the digital space, the CDC National Centre for Injury Prevention and Control (Injury Centre) coached almost 300 attendees in a series of webinars, dedicated to the prospect of instruction in the utility and best use of social media for injury and violence prevention. Through September–December 2014, the webinars covered the topics of why social media for injury and violence prevention, getting started in social media, developing content and engagement, and metrics and evaluation. Methods/Approach: By collaborating with the Safe States organisation, the CDC Injury Centre was able to tap directly into the audience, dedicated to the development and promotion of injury and violence prevention programs. By breaking up the webinars into social media topic-based segments, the trainings were able to reach professionals at any stage of development of their social media programs. At the end of each webinar, the presenter provided opportunities for the attendees to put their new education into practice through suggested homework assignments for their own individual or organisational social media development needs. Results: The webinars have had good registration, attendee, and engagement rates, with unique questions posed by participants. Final assessments will include attendee data on years in the field, comfort level in using social media before and after the series, and overall satisfaction with the information provided in the webinar series. This data will be compiled through registration and post-webinar survey responses. Conclusions: The growing field of injury and violence prevention needs support in social media program and content development. With support from larger organisations, state and local organisations may have the capacity to reach their own constituents though advanced digital and interactive communications. Significance and contribution to the field: With a broader knowledge of how to implement, engage, and measure social media programs, injury and violence professionals will be able to not only reach their audiences with effective prevention messages, but also be able to collaborate across organisations and disciplines more effective prevention communications.